Surface, Deep, and Transfer? Considering the Role of Content Literacy Instructional Strategies - Frey, Nancy; Fisher, Douglas; Hattie, John (Journal of adolescent & adult literacy, 2017)
This article provides an organizational review of content literacy instructional strategies to forward a claim that some strategies work better for surface learning, whereas others are more effective for deep learning and still others for transfer learning. The authors argue that the failure to adopt content literacy strategies by disciplinary teachers may be due, in part, to the mismatch between the approach and the level of learning expected.